LITERASI KEUANGAN DAN PENGELOLAAN KEUANGAN TERHADAP KINERJA KEUANGAN UMKM SEKTOR KULINER KEMASAN - Rahwayu, Dola; Sari, Laynita; Zulvia, Dewi; Umar, Detani; Septiano, Renil (LPPM Universitas Bina Bangsa, 2025)
MSMEs in Indonesia are the basis for the development of the people's economy. This shows that MSMEs are one of the business sectors that can develop and be consistent in the national economy. The purpose of this study is to empirically determine financial literacy and financial management on the financial performance of MSMEs in the culinary packaging sector in Padang Barat District. This study uses a quantitative approach and the sampling technique used is convenence sampling. This study used a sample of 75 MSME actors, the number of data returned was 66 data. Data was obtained from questionnaires distributed to MSME actors in the culinary packaging sector in Padang Barat District. Data processing using SPSS version 26. The results of this study explain that financial literacy and financial management have a positive and significant effect on financial performance,